Identification of Rice Germplasm with Resistance to Bacterial Leaf Blight (Xanthomonas oryzae Pv. Oryzae) - Sharma, B; Pandey, MP (Bangladesh Journal of Agricultural Research, 2012)
Not available DOI: http://dx.doi.org/10.3329/bjar.v37i2.11239 Bangladesh J. Agril. Res. 37(2): 349-353, June 2012